2011
DOI: 10.1016/j.visres.2011.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Collinear facilitation and suppression at the periphery

Abstract: Collinear facilitation is a common phenomenon in the fovea, but it has been recently challenged at the human periphery. Since physiological studies show that facilitation is found at the periphery but only from outside the receptive field, our hypothesis was that facilitation at the periphery exists but from larger target-flanker separations than the fovea. Here, we applied a recent paradigm (Polat & Sagi, 2007) to probe facilitation at the periphery. We used a Yes/No detection task by measuring the false-posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
106
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(132 citation statements)
references
References 70 publications
26
106
0
Order By: Relevance
“…Other studies used a Yes/No task with eccentric stimuli and found collinear facilitation (Lev & Polat, 2011;Maniglia et al, 2011). We attempted to replicate these findings with MD patients since this task may be advantageous when compared to a temporal-2AFC task.…”
Section: Experiments 1: Pl With Yes/no Taskmentioning
confidence: 92%
See 2 more Smart Citations
“…Other studies used a Yes/No task with eccentric stimuli and found collinear facilitation (Lev & Polat, 2011;Maniglia et al, 2011). We attempted to replicate these findings with MD patients since this task may be advantageous when compared to a temporal-2AFC task.…”
Section: Experiments 1: Pl With Yes/no Taskmentioning
confidence: 92%
“…We attempted to replicate these findings with MD patients since this task may be advantageous when compared to a temporal-2AFC task. In fact, the latter may be limited by the requirement to maintain fixation between the two temporal intervals (Lev & Polat, 2011). In independent blocks, stimuli were presented either on the PRL or the non-PRL.…”
Section: Experiments 1: Pl With Yes/no Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…The psychophysics studies by Xing and Heeger (2000) and Petrov et al (2005) both demonstrated that the strength of surround suppression increases with eccentricity up to the 10 • eccentricity that was studied, but their data do not agree on whether surround suppression is present at the fovea. It has also been debated if surround facilitation operates at the peripheral visual field (Xing and Heeger, 2000;Williams et al, 2002;Lev and Polat, 2011). Using electrophysiology, Shushruth et al (2009) quantified surround suppression in macaque V1 and V2, but failed to find significant correlations with eccentricity (within 10 • eccentricity).…”
Section: Spatial Summation Is Similar Across the Visual Fieldmentioning
confidence: 99%
“…Since Polat & Sagi (1993) first demonstrated both facilitation and suppression with such an arrangement, a multitude of spatial (Polat & Sagi 1994;Polat 2009;Polat et al 1998;Zenger-Landolt & Koch 2001;Mizobe et al 2001;Freeman et al 2001;Woods et al 2002;Freeman et al 2004;Giorgi et al 2004;Polat et al 2005;Polat & Sagi 2007;Shani & Sagi 2005;Huang et al 2006;Huang & Hess 2007;Huang et al 2012;Huang & Hess 2008;Sterkin et al 2008;Katkov & Sagi 2010;Wu & Chen 2010;Kéita et al 2011;Lev & Polat 2011;Jachim et al 2015) and temporal (Tanaka & Sagi 1998;Polat & Sagi 2006;Cass & Alais 2006;Huang & Hess 2008;Sterkin et al 2009;Li et al 2010;Sterkin et al 2012) combinations of target and flanker designs have been developed.…”
Section: Introductionmentioning
confidence: 99%